Winning Strategy For Prosperous Justice Party (Pks) Candidate Abdul Aziz Pks Candidate In The 2024 Legislative Election : Case Study Of Abdul Aziz Electoral District 10 Dki Jakarta - Moerdijanto, Muhammad Athallah; Aji , Muhammad Prakoso (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
The 2024 legislative election in Jakarta is an important moment in the dynamics of Indonesian politics, especially for the Prosperous Justice Party (PKS) which won a significant victory. This study aims to analyze the winning strategy of Abdul Aziz, the PKS legislative candidate in the 10th DKI Jakarta Electoral District (Dapil), as well as the factors that contributed to its success.. Using a descriptive qualitative approach, this study examines the effectiveness of political and marketing strategies applied, including community-based approaches, the use of social media, and political communication strategies. The results showed that the strategy carried out by Abdul Aziz focused on the utilization of a loyal mass base, campaigns based on social welfare issues, as well as direct involvement in social and religious activities. In addition, digital communication strategies through social media and the involvement of local leaders also play an important role in improving its electability. This research provides insight into the dynamics of political campaign strategies in the digital age as well as their implications for voter trends in metropolitan areas. The PKS as a moderate Islam-based party also has challenges in extending support beyond its loyal voters. Therefore, the campaign strategy applied is not only based on religious issues, but also emphasizes concrete programs that are relevant to urban problems such as education, health, and infrastructure, which of course is in line with the theory used in this study, namely the theory of political strategy by Peter Schroder, which specifically discusses 3 types of political strategies.